Wokół pamięci Baonu AK „Zośka” i jego żołnierzy w Polsce Ludowej (1945–1989) – wprowadzenie do badań - Rutkowski, Tadeusz (Pamięć i Sprawiedliwość, 2017)
The subject of the article is the analysis of the process of creation of the remembrance of the battles and soldiers of the scout battalion “Zośka” of Armia Krajowa in the social space and the People’s Republic of Poland historiography. This process was commenced during the war, when a group of “Zośka” soldiers undertook actions aimed at preserving the documentation of the battalion. After the intrusion of the Red Army, the soldiers of the battalion mainly conspired against the Communist government and managed to create a headquarters for the battalion on the Powązki military cometary, which along with other headquarters became a place of remembrance for the Uprising and the insurgents. Simultaneously, the first publications were released concerning the “Zośka” battles, including the issue of the book entitled “Kamienie na szaniec” by Aleksander Kamiński, published during the underground movement. The ongoing Stalinisation of Poland interrupted the possibility to commemorate the “Zośka” battalion, the soldiers of which were subjected to repression and persecution. After 1959, fundamental works were published concerning the A. Kamiński’s battalion “Zośka” and “Parasol” and the “Pamiętniki żołnierzy baonu ’Zośka’”, which created a basis for the cultivation of remembrance of the battalion in the public space, as well as outside Warsaw. Despite limitation created by the government, in particular considering the commemoration tablets, historical publications, the remembrance of “Zośka” was cultivated especially among some scout groups. An important moment here was naming the Scouting Organisation of Warsaw Mokotów after the Grey Ranks (Szare Szeregi) and organisation by it the “Arsenał” Treck since 1972. In 1966 a group of the battalion soldiers was created within the Union of Fighters for Freedom and Democracy (ZBoWiD), it gradually became possible to commemorate the military actions of the battalion, although in a wider range it only became possible in the 70s and especially in the 80s. However, the People’s Republic of Poland government tried to limit commemorating the battalion in the public space. The role of remembrance of the “Zośka” battalion in shaping the historical awareness of the Communist Poland is extremely important due to the its range and the moral values it conveyed. Today it is rather underestimated.